First pages - Table of contents - Presentation - Dedication - Aguilar Mora, Sergio (Revista de Biología Tropical, 2021)
The North Pacific and the South Pacific of Nicaragua is a region of great biological, geological, economic and social wealth. There the dry forest mixes with the rain forest, the sea with the islands and nature with the people. It is a region influenced by the Papagayo upwelling, the emergence of cold marine waters during the dry season, which generates an abundance of life in the sea.